(untitled) (Medical Forum Monthly, 2024)
Background: Pulmonary Nocardiosis (PN) is a severe and infrequent infection caused by Nocardia species, pathogen that can behave both as opportunistic as well as infectious with a high morbidity and mortality that mainly affects immunocompromised patients. In recent years, an increase in PN cases has been detected among patients with chronic obstructive pulmonary disease (COPD). The factors that are associated with its presence and determinants of its prognosis remain unknown. The aim of this study is to identify the frequency of nocardia in bronco alveolar lavage fluid (BALF) of patients suffering from chronic obstructive pulmonary disease. Objective: Analyze the bronco alveolar lavage fluid (BALF) of patients suffering from COPD for presence of nocardia and determination of differential leukocyte count. Study Design: Prospective study Place and Duration of Study: This study was conducted at Tertiary Care Hospitals in Karachi from March 2012 till October 2012.. Materials and Methods: It is a prospective study of COPD patients. The study comprises of 140 patients with chronic obstructive pulmonary disease with or without treatment. Results: All patients were divided in two groups A and B according to gender, and each group was further divided according to age i.e. above 40 years and below 40 years. Out of 140 patients 68 turned out to be positive for Nocardia. Conclusion: Nocardiosis is considered to be uncommon in Pakistan, but our study suggests that prevalence of Nocardial infections in patients suffering from COPD is quite high and cases are not restricted to the classical immunocompromised host.